1996
DOI: 10.1021/es950618m
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Chromate Reduction by Ferrous Iron

Abstract: Reduction of Cr(VI) to Cr(III) is environmentally favorable as the latter species is not toxic to most living organisms and also has a low mobility and bioavailability. Ferrous iron is one possible reductant implicated as a major contributor to the removal of Cr-(VI) from suboxic and anoxic waters and soils. Despite the importance of this redox reaction, no mechanistic or kinetic information are available, which are needed to determine the rate of Cr(VI) reduction and to assess the role of oxygen in limiting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
192
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(198 citation statements)
references
References 19 publications
5
192
0
1
Order By: Relevance
“…However, ferrous iron from the Fe III /Fe II redox couple, either in aqueous solution or adsorbed on mineral surfaces, can act as a reductant for organic and inorganic soil components (e.g. MnO 2 ) [77][78][79] and contaminants [80,81]. Furthermore, it has been shown that adsorbed or structural Table 1).…”
Section: Implications For Fe 0 Reactive Wallsmentioning
confidence: 99%
“…However, ferrous iron from the Fe III /Fe II redox couple, either in aqueous solution or adsorbed on mineral surfaces, can act as a reductant for organic and inorganic soil components (e.g. MnO 2 ) [77][78][79] and contaminants [80,81]. Furthermore, it has been shown that adsorbed or structural Table 1).…”
Section: Implications For Fe 0 Reactive Wallsmentioning
confidence: 99%
“…on bentonite is an exothermic process. is exothermic effect can be explained by the forces of interaction between the bentonite and metal, which are stronger than those existing in both bentonite and metal alone, which means that it would prefer the product than reactant [30]. e almost zero values of Δ * suggests that the entropy of the system is decreased or stayed constant.…”
Section: Ermodynamics Of Sorption Onmentioning
confidence: 99%
“…[4,14,22] However, ferrous iron from the Fe 2+ -Fe 3+ redox couple, either in aqueous solution or adsorbed on mineral surfaces, can be part of a convenient delivery path for electrons, reducing and immobilizing organic and inorganic pollutants. [23][24][25][26][27] Furthermore, pollutant coprecipitation with corrosion products has been demonstrated as another removal pathway. [28,29] Therefore there are at least three possible immobilization pathways for several pollutants: reduction by Fe°, by Fe 2+ and coprecipitation with corrosion products.…”
Section: Some Relevant Aspects Of the "Pollutant-zvi-h 2 O"-systemmentioning
confidence: 99%